Uji Organoleptik Yoghurt Susu Sapi yang Diberi Penambahan Tepung Ubi Ungu (Ipomoea batatas) dengan Kadar Berbeda - Febrika Hidayati; Lilis Hartati; Sutarto Sutarto (Jurnal Sains Peternakan Nusantara, 2026)
The growth of microorganisms causes spoiled milk. One of the milk processing technologies that are not easily damaged is the manufacture of yogurt by fermentation method. During the fermentation process, the use of starter lactic acid bacteria such as Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus salivarius account for 10% of total milk. Meanwhile, natural additives used to increase the value of creativity is a natural dye from purple sweet potato flour. The purpose of making cow's milk yogurt can be an alternative to milk processing and physical quality assessment, the level of preference of panelists to yogurt with purple sweet potato flour. Manufacture of cow's milk yogurt plus purple sweet potato flour with a complete randomized design (RAL) of four treatments of five replications, namely concentrations of 0%, 8%, 10%, and 12%. The parameters in this study are color, texture, aroma, taste and overall acceptance. Based on the results of research, the highest average value of color is 12% 4.01, texture is 0% 3.06, aroma is 12% 2.62 and taste is 0% 2.68, while the highest average value of hedonic test is color is 12% 3.72, texture is 0% 3.24, aroma is 0% 3.02, taste is 0% 2.72 and overall acceptance is 0% 3.03. Organoleptic and hedonic tests covering texture, aroma, color, taste, and overall acceptance were significantly different, while the color was not significantly different. It was concluded that the addition of purple yam flour concentration can be used as an additional ingredient in yogurt processing, because it can improve physical characteristics